PDXK mutations cause polyneuropathy responsive to pyridoxal 5′‐phosphate supplementation. Issue 2 (1st July 2019) - Chelban, Viorica; Wilson, Matthew P.; Warman Chardon, Jodi; Vandrovcova, Jana; Zanetti, M. Natalia; Zamba‐Papanicolaou, Eleni; Efthymiou, Stephanie; Pope, Simon; Conte, Maria R.; Abis, Giancarlo; Liu, Yo‐Tsen; Tribollet, Eloise; et al.
Abstract : Objective: To identify disease‐causing variants in autosomal recessive axonal polyneuropathy with optic atrophy and provide targeted replacement therapy. Methods: We performed genome‐wide sequencing, homozygosity mapping, and segregation analysis for novel disease‐causing gene discovery. We used circular dichroism to show secondary structure changes and isothermal titration calorimetry to investigate the impact of variants on adenosine triphosphate (ATP) binding. Pathogenicity was further supported by enzymatic assays and mass spectroscopy on recombinant protein, patient‐derived fibroblasts, plasma, and erythrocytes. Response to supplementation was measured with clinical validated rating scales, electrophysiology, and biochemical quantification. Results: We identified biallelic mutations in PDXK in 5 individuals from 2 unrelated families with primary axonal polyneuropathy and optic atrophy. The natural history of this disorder suggests that untreated, affected individuals become wheelchair‐bound and blind. We identified conformational rearrangement in the mutant enzyme around the ATP‐binding pocket. Low PDXK ATP binding resulted in decreased erythrocyte PDXK activity and low pyridoxal 5′‐phosphate (PLP) concentrations. We rescued the clinical and biochemical profile with PLP supplementation in 1 family, improvement in power, pain, and fatigue contributing to patients regaining their ability to walk independently during the first year of PLP normalization. Interpretation: We show that mutations in PDXK cause autosomal recessive axonal peripheral polyneuropathy leading to disease via reduced PDXK enzymatic activity and low PLP. We show that the biochemical profile can be rescued with PLP supplementation associated with clinical improvement. As B6 is a cofactor in diverse essential biological pathways, our findings may have direct implications for neuropathies of unknown etiology characterized by reduced PLP levels. ANN NEUROL 2019;86:225–240